2017
DOI: 10.11604/pamj.2017.27.135.11924
|View full text |Cite
|
Sign up to set email alerts
|

Grossesse et accouchement des patientes ayant un antécédent de césarienne à Dakar : aspects épidémio-cliniques thérapeutiques et pronostiques

Abstract: Il s’agissait de déterminer la fréquence hospitalière de l’accouchement sur utérus cicatriciel à Pikine, d’évaluer la qualité de la prise en charge anténatale des grossesses sur utérus cicatriciel et de rechercher les facteurs pronostiques de l’issue d’une épreuve utérine. Nous avons procédé à une étude rétrospective à partir de dossiers médicaux et des protocoles opératoires des patientes ayant accouché sur utérus cicatriciel durant la période du 1er Janvier 2010 au 31 Décembre 2011. Ont été analysés les donn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
6
2
Order By: Relevance
“…Women with a scarred uterus and an IGP longer than 24 months accounted for 86.62% of patients. This rate is higher than those of studies by Koulimaya [8] and Nayama [9], who reported 37.9% and 56.8%, respectively. This is due to a variety of reasons: 1) increased practitioner emphasis on family planning counselling and related medical indications of such planning; 2) women's increased awareness of the risks associated with more than one pregnancy within a two-year period; and 3) the increased availability of free contraception in our country over the past three years.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Women with a scarred uterus and an IGP longer than 24 months accounted for 86.62% of patients. This rate is higher than those of studies by Koulimaya [8] and Nayama [9], who reported 37.9% and 56.8%, respectively. This is due to a variety of reasons: 1) increased practitioner emphasis on family planning counselling and related medical indications of such planning; 2) women's increased awareness of the risks associated with more than one pregnancy within a two-year period; and 3) the increased availability of free contraception in our country over the past three years.…”
Section: Discussioncontrasting
confidence: 75%
“…During our study period, 9.96% of patients that delivered had at least one prior caesarean scar. This rate is lower than that of previous studies conducted by Cissé (1.5%) [3], Tshilombo (2.4%) [8], and Dembélé (4.92%) [5]. The high proportion in our study can be attributed to the fact that the majority of high-risk deliveries are referred to our facility, including deliveries via scarred uterus.…”
Section: Discussioncontrasting
confidence: 69%
“…This risk that strikes every Obstetrician explains the ongoing research to achieve the best conditions for a favorable outcome of pregnancy and childbirth [1]. The quote "caesarean one day, caesarean always" stated by D Craigin in 1916 still weighs on any woman with a prior cesarean section when she begins a new pregnancy [2] [3]. The main cause of the cicatricial uterus is a history of cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In most of these countries, this rate is well above 15%, a threshold long defined as optimal by the WHO. This rate varies from around 15% in the Netherlands, Finland and Iceland to more than 40% in Mexico, Turkey, China and Brazil [2] [4] [5]. In France, the rate of caesarean section was 20.8% in 2010 against 15.5% in 1995.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation